Pengaruh Pajak Pertambahan Nilai dan Pajak Kendaraan Bermotor Tarif Progresif terhadap Daya Beli Konsumen - Salma Faizah; Ajimat Ajimat (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2022)
This study aims to determine the effect of Value Added Tax and Progressive Tariff Motor Vehicle Tax on Consumer Purchasing Power. This research was conducted at SAMSAT Bekasi City in 2021. The quantitative research method with a sample of 100 respondents was obtained through the slovin technique. The data analysis technique used descriptive statistical analysis, validity and reliability tests, multiple linear regression, coefficient of determination and hypothesis testing. For quantitative data analysis method, SPSS version 25 is used. Based on the results of the analysis, it is stated that the value added tax has a significant effect on consumer purchasing power with a significance level of 0.043 which is smaller than = 0.05. The progressive rate motor vehicle tax has a significant effect on consumer purchasing power with a significance level of 0.000 which is smaller than = 0.05.